2020
DOI: 10.1101/2020.04.04.025825
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular characterization of selectively vulnerable neurons in Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is characterized by the selective vulnerability of specific neuronal populations, the molecular signatures of which are largely unknown. To identify and characterize selectively vulnerable neuronal populations, we used single-nucleus RNA sequencing to profile the caudal entorhinal cortex and the superior frontal gyrus -brain regions where neurofibrillary inclusions and neuronal loss occur early and late in AD, respectively -from individuals spanning the neuropathological progression of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 98 publications
(167 reference statements)
6
23
0
Order By: Relevance
“…Using bMIND, we estimated sample-level CTS expression and detected CTS-DEGs related to AD with FDR < 0.05 (Supplemental Table S1). Similar to the findings based on snRNA-seq of AD (Mathys et al, 2019), most identified CTS-DEGs were from excitatory neurons, a finding that comports with the observed selective vulnerability of excitatory neurons in the brain of AD samples (Leng et al, 2020). We compared the ExN-DEGs identified by the snRNA-seq study (Mathys et al, 2019) and bMIND from the three bulk datasets (Fig.…”
Section: Cts Differential Expression Analysis Of Brain Tissue From Alsupporting
confidence: 62%
“…Using bMIND, we estimated sample-level CTS expression and detected CTS-DEGs related to AD with FDR < 0.05 (Supplemental Table S1). Similar to the findings based on snRNA-seq of AD (Mathys et al, 2019), most identified CTS-DEGs were from excitatory neurons, a finding that comports with the observed selective vulnerability of excitatory neurons in the brain of AD samples (Leng et al, 2020). We compared the ExN-DEGs identified by the snRNA-seq study (Mathys et al, 2019) and bMIND from the three bulk datasets (Fig.…”
Section: Cts Differential Expression Analysis Of Brain Tissue From Alsupporting
confidence: 62%
“…Subclustering of astrocyte nuclei revealed four subpopulations of cells with one subcluster called Ast1 enriched with AD cells that upregulated GLUL and the AD risk gene CLU (Mathys et al 2019) (Table 1), previously found upregulated in reactive astrocytes in response to neurodegeneration (Shin et al 2006). Recent singlenucleus sequencing of the entorhinal cortex and the superior frontal gyrus from human healthy brains (n = 3), early (n = 4) and advanced (n = 3) stages of AD also revealed an astrocyte subpopulation expressing higher levels of GFAP, called GFAP-high (Leng et al 2021). GFAP-high astrocytes upregulate CD44 and TNC, both involved in interactions with the extracellular matrix; as well as HSPB1 and HSP90AA1, chaperones involved in proteostasis.…”
Section: Astrocyte Genes and Altered Molecular Pathways In Admentioning
confidence: 90%
“…GFAP-high astrocytes upregulate CD44 and TNC, both involved in interactions with the extracellular matrix; as well as HSPB1 and HSP90AA1, chaperones involved in proteostasis. Interestingly, GFAP-high astrocytes downregulated genes involved in glutamate and GABA homeostasis (SLC1A2, SLC1A3, GLUL and SLC6A11) and synaptic adhesion/maintenance (NRXN1, CADM2, PTN and GPC5), indicating they may have compromised homeostatic function (Leng et al 2021) (Table 1).…”
Section: Astrocyte Genes and Altered Molecular Pathways In Admentioning
confidence: 99%
“…Importantly, it was found that although the AD risk gene apolipoprotein E (APOE) was repressed in astrocyte subpopulations and in AD-related oligodendrocyte progenitor cells, it was upregulated in an AD-specific microglial subpopulations within the EC, suggesting that these specialized cells contribute to disease susceptibility of the EC during AD. A selectively vulnerable subpopulation of excitatory neurons in the EC, which shows a corresponding selective depletion as the disease progresses, has also been identified using SnRNA-seq in post-mortem AD brains ( Leng et al, 2020 , preprint). Interestingly, this study identified nuclear receptor RAR-related orphan receptor beta (RORB), which is a developmental driver of neuronal subtype identity ( Jabaudon et al, 2012 ; Oishi et al, 2016 ), as a marker for the selective vulnerability of excitatory EC neurons.…”
Section: Drivers Of Molecular Neurodegeneration and Vulnerability Of mentioning
confidence: 99%